2019
DOI: 10.1139/cjfr-2018-0322
|View full text |Cite
|
Sign up to set email alerts
|

The species-specific responses of nutrient resorption and carbohydrate accumulation in leaves and roots to nitrogen addition in a subtropical mixed plantation

Abstract: Ephemeral tissues such as leaves and fine roots are sensitive to nutrient alteration. Whether nutrient addition can influence the linkage between nutrient resorption and carbohydrate accumulation in leaves and roots is not clear. We measured nitrogen (N) and phosphorus (P) concentrations and nonstructural carbohydrates (NSC) of the <one- and >one-year-old leaves and absorptive and transportive roots in two species of a mixed plantation during the dormant and growing seasons within an N-addition experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…We propose more studies to consider the role of understorey vegetation and soil microbial composition in regulating plant mixture effects on terrestrial C:N:P ratios. We note that both plant and soil stoichiometry strongly depend on plant species due to their specific strategies for the assimilation and allocation of C and to their demand and resorption of nutrients 38 . Therefore, we estimated the effects of species mixture on terrestrial C:N:P by factoring out species-specific influences on plant and soil C:N:P 39 , i.e., the effect of species mixture in each original study was estimated by comparing the observed values in mixtures and the expected responses based on the weighted values of the component species in monocultures.…”
Section: Resultsmentioning
confidence: 94%
“…We propose more studies to consider the role of understorey vegetation and soil microbial composition in regulating plant mixture effects on terrestrial C:N:P ratios. We note that both plant and soil stoichiometry strongly depend on plant species due to their specific strategies for the assimilation and allocation of C and to their demand and resorption of nutrients 38 . Therefore, we estimated the effects of species mixture on terrestrial C:N:P by factoring out species-specific influences on plant and soil C:N:P 39 , i.e., the effect of species mixture in each original study was estimated by comparing the observed values in mixtures and the expected responses based on the weighted values of the component species in monocultures.…”
Section: Resultsmentioning
confidence: 94%
“…To fill these knowledge gaps, a field cable heating experiment was carried out over 4 years in southern China. C. lanceolata is an important tree species for timber forests in subtropical regions because of its wide cultivation area, fast growth rate, and high product quality (Bu et al, 2019). We focused on two questions: (i) how does warming affect the stoichiometric patterns of foliar C:N:P:K:Ca:Mg, non-structural carbohydrate, and stable isotope in C. lanceolata seedlings; and (ii) what are the effects of the stoichiometric homeostasis, non-structural carbohydrate, and stable isotope on the growth of C. lanceolata seedlings under the warming scenarios?…”
Section: Introductionmentioning
confidence: 99%
“…In a 10 year N and P addition experiment, the leaf photosynthesis rate, P, and chlorophyll of two understory species were altered by P addition, suggesting that subtropical forests might be P limited [10]. Moreover, no response of soluble protein, nonstructural carbohydrates, or free amino acids to N addition indicated that understory plants in reforested forests may be limited by light availability rather than N [11]. However, plants evolved to have various leaf traits (morphological, biochemical, and physiological traits) for use, allowing them to adapt to a wide range of ecological gradients [12,13], but few studies reported that multiple leaf traits responded to N and P addition simultaneously.…”
Section: Introductionmentioning
confidence: 99%